Relevance of Law Consumer Protection on Aircraft Post Master Flight Agent - Fitri Pratiwi Rasyid (Faculty of Law, Musamus University, 2019)
At the time of the accident on the Lion Air flight JT 610, there were many ideas to close the flight operating permit. In fact, if reviewed further, for whatever reason, in some